The Relationship between the Intensity of Participating Majelis Taklim and the Level of Religious Knowledge of the Community in Andilan Pasaman District - Marfalak, Marfalak; Solfema, Solfema (Universitas Negeri Padang, 2024)
This research is motivated by the low level of religious knowledge among the Andilan community in Pasaman Regency, allegedly caused by several factors, one of which is the intensity of participating in